(3cJGH GdZfi hGdefis - (3GdMSf Hf fhM GdbeQj GdMcje, CHh efUhQ,J (B380 (3g` s ((3CMeO Hf GdfLjH GdWHjH s)
(3ChdgG (B:s
(3bGd Efi de CRd ai UHGi hefP YbdJ CLfi GdYdhe GdWHjYjI NUhUkG Yde GdWH deG cfJ CQi ajg CQGMI ddCfaS s
(3BNQgG (B:s
(3hde CPcQ ai gPG GdcJGH OhGA eQcHkG ef eYLhf Ch bQU s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1210s
Keywords: (3GdWHs